Innovative local and regional economic development initiatives in Latin America: a review - Helmsing, A. H. J. Bert (Interações, 2016)
In the past fifteen years local regional development (LRD) policies have changed considerably in focus andcontent. New actors came to be involved or involved themselves in such policies. Currently, we find ourselves in a thirdgeneration of LRD policies. Central tenets of these policies are: i) meso-institutions; ii) interventions focusing onenterprise development, communities and localities; iii) actors and networking; and iv) learning processes. Thepurpose of this article is to review a series of innovative programmes in order to examine to what extent they sharesome of these common tenets.